2009
DOI: 10.1111/j.1750-3841.2009.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yolk Contamination, Shearing, and Heating on Foaming Properties of Fresh Egg White

Abstract: A series of experiments were conducted to evaluate effects of yolk contamination, shearing, and thermal treatment on foaming properties of liquid egg white. Samples obtained from industrial processing were also evaluated. Whipping and purging methods were both used to assess their effectiveness and sensitivity in evaluating foaming. A concentration as low as 0.022% (as-is basis) of yolk contamination caused significant reductions in foaming capacity and foaming speed. The neutral lipid fraction of egg yolk cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 28 publications
0
18
1
Order By: Relevance
“…In addition, there is practically no tolerance level for yolk contamination, i.e. even at the lowest testing concentration (0.01% yolk in white protein, as‐is basis) foaming was significantly reduced 1. This research also showed that neutral oil, rather than the polar phospholipids in the yolk, is the main contributor for reduced foaming.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…In addition, there is practically no tolerance level for yolk contamination, i.e. even at the lowest testing concentration (0.01% yolk in white protein, as‐is basis) foaming was significantly reduced 1. This research also showed that neutral oil, rather than the polar phospholipids in the yolk, is the main contributor for reduced foaming.…”
Section: Introductionmentioning
confidence: 72%
“…The 0.4% yolk addition was used to simulate yolk contamination of the egg white for this study. The use of this level was determined based on the findings from our previous work,1 which showed that 0.4% yolk (as‐is basis) led to the lowest foaming performance (reached steady state) as measured by the purging method, but this level was still on the decline in performance as measured by the whipping method. The 0.4% yolk addition may represent a severe case of contamination in the industry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang and Wang (2009a) reported that the neutral lipid fraction (triacylglycerols) reduced foaming capacity at levels as low as 0.022% (w/w), but polar lipids had no effect at levels as high as 0.1%. Of the factors examined (pumping, pasteurization, storage), yolk contamination had the greatest effect on foaming performance.…”
Section: Introductionmentioning
confidence: 99%